2016
DOI: 10.1016/j.cellsig.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Repressed PKCδ activation in glycodelin-expressing cells mediates resistance to phorbol ester and TGFβ

Abstract: Glycodelin is a glycoprotein mainly expressed in well-differentiated epithelial cells in reproductive tissues. In normal secretory endometrium, the expression of glycodelin is abundant and regulated by progesterone. In hormone-related cancers glycodelin expression is associated with well-differentiated tumors. We have previously found that glycodelin drives epithelial differentiation of HEC-1B endometrial adenocarcinoma cells, resulting in reduced tumor growth in a preclinical mouse model. Here we show that gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We have suggested that glycodelin also acts as a tumor suppressor protein, at least in endometrial carcinoma, based on our findings showing that glycodelin transfection in HEC-1B human endometrial carcinoma cells cause morphological reversion from malignant phenotype to a more normal state [19][20][21]. This is mediated by a repressed PKCδ activation [21]. Furthermore, in a preclinical mouse model, glycodelin-induced differentiation brought about reduced tumor growth [20].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…We have suggested that glycodelin also acts as a tumor suppressor protein, at least in endometrial carcinoma, based on our findings showing that glycodelin transfection in HEC-1B human endometrial carcinoma cells cause morphological reversion from malignant phenotype to a more normal state [19][20][21]. This is mediated by a repressed PKCδ activation [21]. Furthermore, in a preclinical mouse model, glycodelin-induced differentiation brought about reduced tumor growth [20].…”
Section: Introductionmentioning
confidence: 81%
“…HEC-1B cells (ATCC HTB-113), which do not normally produce glycodelin, were stably transfected with glycodelin cDNA [20,21]. This cell line is a subline [33] of HEC-1 cells derived from a moderately differentiated papillary adenocarcinoma tumor from a patient with stage IA endometrial cancer [34].…”
Section: Production and Purification Of Glycodelinmentioning
confidence: 99%